Thermal-Hydraulic Network Model for steady-state thermal analysis and design of power transformer magnetic cores - L.H. Medeiros; M.M. Oliveira; C.E.G. Falcão; V.C. Bender; T.B. Marchesan (Case Studies in Thermal Engineering)
The safe operation of power transformers is related to their internal temperatures, which increase due to the heat generated in their active part. The core is subjected to hysteresis, eddy current and stray losses, which lead to its heating and the temperature rise. This paper presents a TH model for determining temperatures along the magnetic cores of power transformers. The inclusion of the transformer’s magnetic core in thermal modeling is of paramount importance due to its significant impact on the overall thermal performance and reliability of the transformer. Traditional thermal models predominantly focus on the oil flow and windings, overlooking the core’s contribution to heat generation and dissipation. Based on the constructive and operational data, the model determines the complete oil flow and temperature distributions over the columns, yokes, and joints by iteratively solving an algorithm composed of hydraulic and thermal resistance networks. The constructive characteristics, as the stacking sheets forming different steps and the anisotropy for heat transfer in different directions, are considered. The analytical results are compared to experimental measurement using an optical fiber sensor allocated in the core of a prototype transformer, indicating that the model can satisfactorily predict the hydraulic and thermal behaviors of magnetic cores.